Impaired Prefrontal-Amygdala Pathway, Self-Reported Emotion, and Erection in Psychogenic Erectile Dysfunction Patients With Normal Nocturnal Erection - Chen, Jianhuai; Chen, Yun; Gao, Qingqiang; Chen, Guotao; Dai, Yutian; Yao, Zhijian; Lu, Qing (Frontiers in Human Neuroscience, 2018)
Background: Neuroimaging studies have demonstrated that the prefrontal cortex and amygdala play an important role in sexual arousal (SA). However, little is known about the interactions between the prefrontal and cortex amygdala, which mediate the cognitive regulation of emotion and SA. Objective: We seek to determine whether nocturnal erection of psychogenic erectile dysfunction (pED) patients are normal and whether there are changes of topological organization in the prefrontal-amygdala pathway of brain network in pED. In addition, whether there are correlations between network property changes and self-reported emotion and erection. Design, setting, and participants: We used the RigiScan device to evaluate erectile function of patients and employed diffusion MRI and graph theory to construct brain networks of 21 pED patients and 24 healthy controls. Outcome Measurements and Statistical Analysis: We considered 4 nodal metrics and their asymmetry scores, and nocturnal penile tumescence (NPT) parameters, to evaluate the topological properties of brain networks of pED and their relationships with the impaired self-reported emotion and erection. Results and Limitations: All the pED patients showed normal nocturnal penile erection, however impaired self-reported erection and negative emotion. In addition, patients showed lower connectivity degree and strength in the left prefrontal-amygdala pathway. We also found that pED exhibited lower leftward asymmetry in the inferior frontal gyrus. Furthermore, patients showed more hub regions and fewer pivotal connections. Moreover, the degree of the left amygdala of pED showed significantly negative correlation with the self-reported erection and positive correlation with the self-reported negative emotion. Conclusions: Together, these results suggest normal nocturnal erection in pED. However, abnormalities of brain network organization in pED, particularly in the left prefrontal-amygdala pathway, are associated with the impaired self-reported erection and negative emotion.